2023
DOI: 10.2478/johh-2023-0028
|View full text |Cite
|
Sign up to set email alerts
|

Monthly stream temperatures along the Danube River: Statistical analysis and predictive modelling with incremental climate change scenarios

Pavla Pekárová,
Zbyněk Bajtek,
Ján Pekár
et al.

Abstract: The aim of the study is to analyse changes and predict the course of mean monthly water temperatures of the Danube River at various locations for the future. The first part of the study involves conducting a statistical analysis of the annual and monthly average air temperatures, water temperatures, and discharges along the Danube River. The study examines long-term trends, changes in the trends, and multiannual variability in the time series. The second part of the study focuses on simulating the average mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…and the respective basin area A in square kilometres (km 2 ). The literature on the Danube River and its catchment water temperature is extensive [7,[44][45][46][47][48][49][50][51][52]. Analysis of Danube water temperature in Austria by Webb and Nobilis concluded that there were significant increases in annual mean values, closely following changes in air temperature [44].…”
Section: Study Areamentioning
confidence: 99%
“…and the respective basin area A in square kilometres (km 2 ). The literature on the Danube River and its catchment water temperature is extensive [7,[44][45][46][47][48][49][50][51][52]. Analysis of Danube water temperature in Austria by Webb and Nobilis concluded that there were significant increases in annual mean values, closely following changes in air temperature [44].…”
Section: Study Areamentioning
confidence: 99%